2021
DOI: 10.1093/gerona/glab236
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Therapy Is Effective at Improving Short- and Long-Term Mobility, Activities of Daily Living, and Balance in Older Patients Following Hip Fracture: A Systematic Review and Meta-Analysis

Abstract: Background A systematic review and meta-analysis was performed to evaluate the short- and long-term effect of exercise therapy on physical function, independence and wellbeing in older patients following hip fracture, and secondly, whether the effect was modified by trial level characteristics such as intervention modality, duration and initiation timepoint. Methods Medline, CENTRAL, Embase, CINAHL and PEDro was searched up-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“… 41 , 44 , 45 , 46 In these studies, as in ours, the amount of physical activity was evaluated with self‐reported questionnaires, and thus the results should be interpreted with caution. In the systematic review of Hulsbæk et al, 47 a small, but nonsignificant effect of exercise on physical activity was observed. A cohort study reported old age and frailty to be explanatory variables for unchanged physical activity levels (number of physical activity sessions per week or month) among home‐dwelling patients with hip fractures.…”
Section: Discussionmentioning
confidence: 94%
“… 41 , 44 , 45 , 46 In these studies, as in ours, the amount of physical activity was evaluated with self‐reported questionnaires, and thus the results should be interpreted with caution. In the systematic review of Hulsbæk et al, 47 a small, but nonsignificant effect of exercise on physical activity was observed. A cohort study reported old age and frailty to be explanatory variables for unchanged physical activity levels (number of physical activity sessions per week or month) among home‐dwelling patients with hip fractures.…”
Section: Discussionmentioning
confidence: 94%
“…Compared to pre-fracture, there is a decrease in ADL [ 44 ]. A systematic review found that rehabilitation has a small-to-moderate effect on ADL in the short and long term (1 year) [ 13 ]. This review also showed a small effect of rehabilitation after hip fracture on HRQoL in the short and long term.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, what type of exercise that is most beneficial for this population is not fully explored [ 11 , 12 ]. A lack of high-quality RCTs’ exploring the effects of rehabilitation after hip fractures among older people has also been identified [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, dementia was reported to significantly negatively impact postoperative walking ability [4]. In 2022, rehabilitation intensity was reported to affect activities of daily living (ADL) [5].…”
Section: Introductionmentioning
confidence: 99%